2014
DOI: 10.1111/apa.12772
|View full text |Cite
|
Sign up to set email alerts
|

Food hypersensitivity is common in Swedish schoolchildren, especially oral reactions to fruit and gastrointestinal reactions to milk

Abstract: Reported food hypersensitivity was common among Swedish schoolchildren. The most frequent symptom expressions were oral symptoms triggered by fruits and gastrointestinal symptoms triggered by milk. The high prevalence of reported symptoms should be validated by clinical examinations to provide a diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The cumulative incidence of reported food allergy or food intolerance in our study was at about the same level as in another Swedish study where 21% of children aged seven to eight years reported food allergy or food intolerance . Oral symptoms were the most frequently reported symptoms in their study, which contrasted with the low cumulative incidence of OAS in our study.…”
Section: Discussionsupporting
confidence: 69%
“…The cumulative incidence of reported food allergy or food intolerance in our study was at about the same level as in another Swedish study where 21% of children aged seven to eight years reported food allergy or food intolerance . Oral symptoms were the most frequently reported symptoms in their study, which contrasted with the low cumulative incidence of OAS in our study.…”
Section: Discussionsupporting
confidence: 69%
“…Endocrine influences have been suggested to contribute to this switch during adolescence [ 19 ]. In our cohort, reported FHS was more common among girls already at 8 years of age, mainly due to a higher female prevalence of FHS to cow´s milk [ 26 ]. This gender difference is in line with a recent Canadian study, where more women than men reported symptoms of lactose intolerance [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Family history of allergy [2325] and allergic diseases in early life, particularly eczema [23] and Immunoglobulin E (IgE) reactivity [2427], are established risk factors, whereas early life environmental factors and socio-demographic exposures remain incompletely understood [23, 2530]. Less is known about the risk factors for, and the prognosis of FRS and FA from early life through adolescence.…”
Section: Introductionmentioning
confidence: 99%